Posterior Ischaemic Optic Neuropathy (Pion) Secondary To Distal Segment Stenosis Of The Left Ophthalmic Artery: A Rare Case Report - Hernawan Hernawan; Delta Iswara; Hasna Okta Asyrofi (CV. AFDIFAL MAJU BERKAH, 2026)
Ischaemic optic neuropathy (ION) is a vision-threatening condition caused by impaired arterial blood supply to the optic nerve. Posterior ischaemic optic neuropathy (PION) is a rare subtype that often presents without funduscopic abnormalities in the acute phase, making diagnosis challenging. We report a case of a 50-year-old man who presented with sudden, painless monocular visual loss in the left eye, accompanied by hemisensory deficits. Ophthalmic examination revealed no optic disc abnormalities, while automated perimetry demonstrated an inferior arcuate visual field defect. Brain magnetic resonance imaging showed a right corona radiata infarction, and digital subtraction angiography confirmed stenosis of the distal branches of the left ophthalmic artery. These findings supported the diagnosis of PION secondary to ophthalmic artery stenosis, an uncommon etiology of ION. The patient had uncontrolled hypertension as a major vascular risk factor and was treated with antiplatelet therapy, resulting in clinical improvement of visual acuity. This case highlights the importance of comprehensive vascular evaluation in patients with suspected PION and emphasizes ophthalmic artery stenosis as a rare but significant cause of ischaemic optic neuropathy. Early recognition of the underlying vascular pathology may facilitate appropriate management and help prevent further ischemic complications.